1978
DOI: 10.1136/hrt.40.12.1371
|View full text |Cite
|
Sign up to set email alerts
|

Observations on intravenous administration of lignocaine in patients with myocardial infarction.

Abstract: suMMARY Lignocaine was administered intravenously to 36 patients with acute myocardial infarction.A bolus of 100 mg followed by an infusion of 2 mg/minute failed to maintain plasma levels above 2 ,g/ml. A bolus of 100 mg followed by 4 mg/minute also failed to maintain satisfactory plasma concentrations during the first hour of therapy.A bolus of 75 mg was combined with an infusion of 10 mg/minute for 20 minutes followed by 1.5 mg/ minute. Satisfactory plasma concentrations during the first hour were observed i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1981
1981
2015
2015

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…Mexiletine is effective in treating ventricular arrhythmias (Campbell et al, 1973;Talbot et al, 1973). It has, however, some cardiac adverse effects (Table III); for example, Cocco and colleagues (1980) reported that it induced atypical ventricular arrhythmia not associated with QTc prolongation.…”
Section: Absence Of Adverse Effectsmentioning
confidence: 99%
“…Mexiletine is effective in treating ventricular arrhythmias (Campbell et al, 1973;Talbot et al, 1973). It has, however, some cardiac adverse effects (Table III); for example, Cocco and colleagues (1980) reported that it induced atypical ventricular arrhythmia not associated with QTc prolongation.…”
Section: Absence Of Adverse Effectsmentioning
confidence: 99%